Development of a Mother and Toddler Class Model Based on Local Wisdom As an Innovation for Stunting Prevention in Limboto District, Gorontalo Regency: a quasi-experimental study - Dewi Modjo; Wiwi Susanti Piola; Rini Wahyuni Mohamad (Poltekkes Kemenkes Palu, 2025)
Background: Stunting prevention programs based on local wisdom consider socio-cultural factors to ensure sustainability. This study analyzes the impact of a mother and toddler class model incorporating local resources—specifically tilapia fish (porridge and nuggets) and moringa leaves (pudding)—as innovative interventions for stunting prevention in Limboto District, Gorontalo Regency. Methods: This research is a quantitative study using a quasi-experimental design with a one-group pre-test and post-test research design. Probability sampling was used with a total of 43 samples. Results: Statistical analysis revealed a significant improvement in maternal knowledge and attitudes regarding local wisdom-based complementary feeding (MPASI), with mean scores rising from 7.44 (SD=1.84) to 9.21 (SD=2.08) with a significance value 0.000 (p<0.05) and a t-score of -1.371. Maternal parenting patterns also improved significantly from a mean of 8.13 (SD=2.12) to 9.51 (SD=2.26) with a significance value of 0.000 (p<0.05) and a t-score of -6.437 at the Limboto Health Center, Gorontalo Regency. Conclusion: This study is expected to contribute to the understanding of stunting prevention by considering the importance of nutritional interventions, health education, and the reduction of stunting rates.